2021
DOI: 10.3390/ma15010213
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Cefixime Trihydrate by Bismuth Ferrite Nanoparticles

Abstract: The present work was carried out to synthesize bismuth ferrite (BFO) nanoparticles by combustion synthesis, and to evaluate the photocatalytic activity of synthesized bismuth ferrite nanoparticles against cefixime trihydrate. BFO nanoparticles were successfully synthesized using bismuth (III) nitrate and iron (III) nitrate by a combustion synthesis method employing different types of fuels such as maltose, succinic acid, cinnamic acid, and lactose. The effects of the different types of fuels on the morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…This feature is attributed to the confluence of Fe–O and Bi–O stretching and bending vibrations within the BO 6 octahedra of the perovskite structure . Additionally, a small hump near 700 cm –1 is linked to the Bi–O stretching and bending vibration. The hump at approximately 865 cm –1 is indicative of the entrapped NO 3 ions. The presence of a metal-oxide band within the 400–700 cm –1 interval corroborates the formation of the perovskite structure, a finding supported by other BFO-based material studies. Furthermore, Ke et al have identified the absorption bands in the 400–600 cm –1 spectral region as fundamental peaks for metal oxides, confirming the successful synthesis of BFO perovskite materials. …”
Section: Resultsmentioning
confidence: 99%
“…This feature is attributed to the confluence of Fe–O and Bi–O stretching and bending vibrations within the BO 6 octahedra of the perovskite structure . Additionally, a small hump near 700 cm –1 is linked to the Bi–O stretching and bending vibration. The hump at approximately 865 cm –1 is indicative of the entrapped NO 3 ions. The presence of a metal-oxide band within the 400–700 cm –1 interval corroborates the formation of the perovskite structure, a finding supported by other BFO-based material studies. Furthermore, Ke et al have identified the absorption bands in the 400–600 cm –1 spectral region as fundamental peaks for metal oxides, confirming the successful synthesis of BFO perovskite materials. …”
Section: Resultsmentioning
confidence: 99%
“…To quantitatively analyse the degradation kinetics, the MB degradation-rate constant (k) was determined by fitting the kinetic data obtained from the linear fitting curves of -ln(C/C0) versus irradiation time (Figure 9B). The excellent linearity of the plots indicates that the photodegradation rate of MB follows a pseudo-first-order kinetic reaction: -ln(C/C0) = kt, where k represents the photodegradation-rate constant (Nazir et al, 2021). Furthermore, the calculated MB degradation efficiency and degradation-rate constant (k) were plotted against the energy bandgap of the ZrO 2-x N x samples in Figure 10.…”
Section: Photocatalytic Activity Assessmentmentioning
confidence: 97%
“…In the IR spectrum of BiFeO 3 , two significant bands were identified. One prominent peak appeared at 560 cm −1 , attributed to Fe-O stretching, while another was observed at 440 cm −1 , related to O-Fe-O vibrations of FeO 6 groups within the perovskite compounds [29].…”
Section: Characterization Of Bifeomentioning
confidence: 99%
“…In the context of studying photocatalysis, the percentage of pollutant decolorization in water was quantified using the well-defined Equation (1) [29]:…”
Section: Photocatalytic Behavior Of Bifeo 3 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation